1994
DOI: 10.2466/pms.1994.79.1.520
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Awareness of Sleep Hygiene in Rotating Shift Workers: Arming Law-Enforcement Officers against Impaired Performance

Abstract: Research into the effects of rotating shift work on health, social, and performance indices suggests significantly more health concerns and judgement errors and poorer sleep patterns in shift workers on rotating versus nonrotating schedules. 31 male and 7 female law-enforcement officers voluntarily participated in a training session on sleep hygiene practices. On the Sleep Hygiene Awareness and Practice Scale administered prior to and after training were significant increases in awareness of sleep hygiene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…Nevertheless, the efficacy of both BCTs is consistent with previous studies using no-treatment controls [17,31,35]. Furthermore, research suggests sleep hygiene knowledge only partially explains sleep hygiene practices [6], and does not guarantee performance [52,53].…”
Section: Limitationssupporting
confidence: 86%
“…Nevertheless, the efficacy of both BCTs is consistent with previous studies using no-treatment controls [17,31,35]. Furthermore, research suggests sleep hygiene knowledge only partially explains sleep hygiene practices [6], and does not guarantee performance [52,53].…”
Section: Limitationssupporting
confidence: 86%
“…Previous studies suggest that rotating shift workers suffer greater sickness and absenteeism than workers assigned to steady shifts, especially when the hours are long (Holbrook et al, 1994). Research has also found negative associations between rotating schedules and employee productivity, safety and accident-proneness (Johnson et.…”
Section: Work Schedulesmentioning
confidence: 91%
“…Hicks, Lucero-Gorman, Bautista, and Hicks (1999) observed sleep hygiene knowledge and practices over several ethnic groups, and found that sleep hygiene knowledge was generally lower than sleep hygiene practices. In addition, Holbrook, White, and Hutt (1994) found that an increase in sleep hygiene knowledge and awareness did not correspond to an increase in sleep hygiene practices, further suggesting that factors other than knowledge play a role in determining sleep hygiene behaviour.…”
Section: Introductionmentioning
confidence: 91%